2014
DOI: 10.1186/1865-1380-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of emergency department crowding on triage destination

Abstract: BackgroundEmergency Department (ED) crowding has been studied for the last 20 years, yet many questions remain about its impact on patient care. In this study, we aimed to determine if ED crowding influenced patient triage destination and intensity of investigation, as well as rates of unscheduled returns to the ED. We focused on patients presenting with chest pain or shortness of breath, triaged as high acuity, and who were subsequently discharged home.MethodsThis pilot study was a health records review of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
1
24
1
1
Order By: Relevance
“…12 In O'Connor et al study, 52% were referred to the ED during peak hours. 10 In our study, the mortality rate was relatively higher than other similar studies, which may be due to including critical patients with higher mortality rate in our study. Moreover, poor treatment facilities could be another potential reason.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…12 In O'Connor et al study, 52% were referred to the ED during peak hours. 10 In our study, the mortality rate was relatively higher than other similar studies, which may be due to including critical patients with higher mortality rate in our study. Moreover, poor treatment facilities could be another potential reason.…”
contrasting
confidence: 54%
“…9 In O'Connor et al study 53.8% were men. 10 In another study, the mean age was 65 and 56.8% were men. 11 In Pines et al study, 57.0% were men with the mean ± SD age of 44 ± 17 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The effects of overcrowding in EDs has led to increased wait times and increased concerns that patient outcomes will suffer. [4][5][6][7] One study found that during crowded conditions, patients with higher acuity such as chest pain or shortness of breath had longer wait times and were inappropriately roomed in non-monitored ED beds. In fact, overcrowding has been associated with increased patient mortality, delayed antibiotic administration, delayed resuscitation efforts, and poor pain management.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, overcrowding has been associated with increased patient mortality, delayed antibiotic administration, delayed resuscitation efforts, and poor pain management. [7] In order to maintain quality care for ED patients, a joint committee of the Emergency Nurses Association (ENA) and the American College of Emergency Physicians (ACEP) encouraged the use of the Emergency Severity Index (ESI). [8] It is the most widely used triage system in the United States and is becoming more widely used in other non English speaking countries.…”
Section: Introductionmentioning
confidence: 99%